EVALUATION OF INTERNSHIP/INTERNS FROM THE PERSPECTIVE OF HUMAN RESOURCES MANAGERS: THE CASE OF KUŞADASI HOSPITALITY BUSINESSES (Third Sector Social Economic Review, 2024)
The tourism sector needs qualified employees trained by educational institutions. Internship, which is considered an important part and complement of tourism education, involves cooperation between educational institutions and the sector and is aimed at meeting the need for human resources.  In this research, it is aimed to evaluate high school and university students who are internships in Kusadasi hospitality businesses by their human resources department managers. In this context, the study group of the research consists of ten hospitality businesses that provide internship opportunities to students in Kusadasi district. Semi-structured interview technique, one of the qualitative research methods, was used in the research. The interviews took place face to face between July 2023 and January 2024. The interviews were recorded with the consent of the participants and then transcribed for content analysis. As a result of the content analysis, it was concluded that hospitality businesses gave priority to nearby regional schools in selecting interns, high school students were preferred more than university students, the theoretical training students received at school was evaluated as insufficient, and intern students were given easier jobs than other employees. Compared to the results of the research conducted in previous years, it has been determined that there have been positive developments in the personal rights of intern students.In the research, findings on the negative consequences of emotional relationships between female students and staff were also obtained. In addition, it has been stated as an important problem that students staying in the area where the hospitality businesses are located behave like other employees of the business. According to the results of the research, some suggestions have been made to the sector and educational institutions.
Keywords: Tourism Education; Internship; Sector - Education Cooperation; Human Resource